Semiotical blues: artifícios da temporalidade nostálgica - CASTRO, Fábio Fonseca de (Universidade Federal do Rio de Janeiro, 2022)
The article reflects on the artifice of temporality in contemporary culture. We start from a “pre-ethno graphic” exploration about ball of nostalgia (baile da saudade), traditional parties present in Belém, Brazil, characterized by remastering of songs the years 1970-1990 and peculiar modes of sociability, to discuss the the persistence of nostalgic sensitivity, structuring the contemporary intersubjective tissue. From a type-ideal, which we call semiotical blues, we seek to understand the structural ele ments of this nostalgic sensibility: the artifice of its narrative temporality, or rather, its temporality as a narrative device. We used as key reference in the conduct of our thinking, the thought of M. Heidegger about everyday temporality, that of J. Derrida on the issue of “metaphysics of presence” and the phenomenological perspective of A. Schutz, in the perception of experience reserves and structures of relevance, present in the intersubjective processes and thus, produces the culture.